PENERAPAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISION PADA MATERI KEBERAGAMAN MAKHLUK HIDUP DI LINGKUNGANKU UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 17 PIDIE - Gusti Handayani (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This study aims to improve student learning outcomes by applying the Student Teams Achievement Division (STAD) model to the material on the diversity of living things in my environment for fourth grade students of MIN 17 Pidie. This type of research is Classroom Action Research (CAR) with the research subjects being grade IV students of MIN 17 Pidie in the 2019/2020 academic year totaling 35 students. Data collection techniques in this study were carried out using observation sheets, tests, field notes and documentation. The results showed that the application of the Student Teams Achievement Division (STAD) model on the diversity of living things in my environment could improve the learning outcomes of fourth grade students of MIN 17 Pidie. This is evident from the research showing that the average value of the first cycle is 62.28, an increase in the second cycle is 69.28 and it increases again in the third cycle, which is 90.